Kajian Pola Morfologi Berdasarkan Kearifan Lokal Desa Adat Jangga Dolok Kabupaten Toba Sumatera Utara - Theresia Permatasari Gurning; Nurini Nurini (Jurusan Perencanaan Wilayah dan Kota, 2023)
Abstract: Jangga Dolok Traditional Village is one of the oldest Batak villages in Toba Regency, North Sumatra. This village is approximately 250 years old and was formed communally by a group of people with the same upstream vision. The purpose of this study was to examine the morphological pattern of the village based on local wisdom that developed in accordance with the traditions that have existed since the days of the Jangga Dolok Traditional Village by identifying non-physical factors and physical factors.The results of this study are that according to the traditional elders of Jangga Dolok Village, residential areas should be placed in hilly areas to avoid dangers such as wild animals and disasters. Meanwhile, agricultural areas such as rice fields and fields are in areas with flat topography. If viewed from the pattern of the settlement area, Jangga Dolok Village includes an elongated or linear pattern settlement that is formed following a road pattern with an irregular road network system or an irregular pattern. Based on its morphology, this village is a ribbon shaped city. The most important factor in the development of this village is the transportation route and the pattern of settlement, causing this area to be rectangular or elongated. Jangga Dolok Village which is formed traditionally cannot be separated from the existence of traditions and local wisdom that indirectly help shape the pattern of the village